Economic and regulatory instruments to control nitrogen pressure. (October 2014) - Le Goffe, P.; Donnars, C.
<x content-type="archive" xml:space="preserve">Abstract</x> This article examines how the concerns of economic efficiency and of redistribution can be integrated into the design of the policies that aim to control the nitrogen flows. Generally speaking, the economists recommend to determine the degree of pollution and to arbitrate between the gains and the transaction costs associated to the implementation of the policy. Regarding instruments, the reduction of the diffuse nitrogen pollution needs a quantitative or economic instrument owing to the difficulty of valuing the environmental efforts of the producers on markets. Unlike for pesticides, the quota is here preferred to the tax, in particular in the case of fertilisers. The polluter-payer principle should be applied to the risks of accidental pollution on livestock farms. Results of a long process under the European Commission pressure, the policies of EU members in Northern Europe are more in line with the economic prescriptions than those of France. Recent evolutions go nevertheless forward, even if penalties for enforcing the practices standards are always missing.